A meta‐analysis of prevalence estimates and moderators of low bone mass in people with schizophrenia. (10th July 2014) - Stubbs, B.; De Hert, M.; Sepehry, A. A.; Correll, C. U.; Mitchell, A. J.; Soundy, A.; Detraux, J.; Vancampfort, D.
<x xml:space="preserve">Abstract</x> Objective To assess the prevalence and moderators of low bone mass, osteopenia and osteoporosis in schizophrenia patients. Method Major electronic databases were searched from inception till December 2013 for studies reporting the prevalence of low bone mass (osteopenia + osteoporosis = primary outcome), osteopenia or osteoporosis in schizophrenia patients. Two independent authors completed methodological appraisal and extracted data. A random effects meta‐analysis was utilized. Results Nineteen studies were included (n = 3038 with schizophrenia; 59.2% male; age 24.5–58.9 years). The overall prevalence of low bone mass was 51.7% (95% CI = 43.1–60.3%); 40.0% (CI = 34.7–45.4%) had osteopenia and 13.2% (CI = 7.8–21.6%) had osteoporosis. Compared with controls, schizophrenia patients had significantly increased risk of low bone mass (OR = 1.9, CI = 1.30–2.77, P < 0.001, n = 1872) and osteoporosis (OR = 2.86, CI = 1.27–6.42, P = 0.01, n = 1824), but not osteopenia (OR = 1.33, CI = 0.934–1.90, P = 0.1, n = 1862). In an exploratory regression analysis, older age (P = 0.004) moderated low bone mass, while older age (P < 0.0001) and male sex (P < 0.0001) moderated osteoporosis. The subgroup analyses demonstrated high heterogeneity, but low bone mass was less prevalent in North America (35.5%, CI = 26.6–45.2%) than Europe (53.6%, CI = 38.0–68.5%) and Asia (58.4%, CI = 48.4–67.7%), and in mixed in‐/out‐patients (32.9%, CI = 49.6–70.1%) vs. in‐patients (60.3%, CI = 49.6–70.1%). Conclusion Reduced bone mass (especially osteoporosis) is significantly more common in people with schizophrenia than controls.